2015
DOI: 10.4103/0976-9668.166076
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study evaluating utility of Mannheim peritonitis index in predicting prognosis of perforation peritonitis

Abstract: Aims:We aimed to validate Mannheim peritonitis index (MPI) for prediction of outcome in patients with perforation peritonitis.Materials and Methods:A prospective study involving 100 subjects operated for perforation peritonitis over the period of 2 years was designed. Postevaluation of predesigned performa, MPI score was calculated and analyzed for each patient with death being the main outcome measure. The MPI scores were divided into three categories; scores <15 (category 1), 16-25 (category 2), and >25 (cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Rajendra Singh Jhobta et al (Kumar et al, 2017), in their study, observed 84% of males as the majority for Perforation Peritonitis. Similarly, Ranjan et al (2015) found 52% males and 48% females. Moreover, Rodolfo L et al, in their investigation seen that appendicular perforations were 48.28% while among 2.87% cases, gastric pathology and small bowel pathology were available and colonic pathology was found among 2.30%.…”
Section: Literature Reviewmentioning
confidence: 86%
See 1 more Smart Citation
“…Rajendra Singh Jhobta et al (Kumar et al, 2017), in their study, observed 84% of males as the majority for Perforation Peritonitis. Similarly, Ranjan et al (2015) found 52% males and 48% females. Moreover, Rodolfo L et al, in their investigation seen that appendicular perforations were 48.28% while among 2.87% cases, gastric pathology and small bowel pathology were available and colonic pathology was found among 2.30%.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Demographic data such as gender, age, aetiology of peritonitis, and hospitalization days were (Jhobta et al, 2006) Diffuse: 83% Localised: 17% (Ranjan et al, 2015) Diffuse: 34.49 % Localised: 65.5% also collected from cases. Investigations such as complete blood count, biochemical analysis of blood, microbiology for serology, X-ray of erect abdomen, CT scan (abdomen/pelvis) / ultrasonography (abdomen/pelvis) were carried out wherever necessary.…”
Section: Source Of Data and Sample Sizementioning
confidence: 99%
“…Independent study variables for MPI scoring system included: age in completed years, sex, malignancy (present/absent), organ failure (present/absent), evolution time (>24 hours/<24 hours), extension of peritonitis (localized/diffuse), origin of sepsis (noncolonic/colonic), character of exudates (clear/faecal/purulent) as described previously (12)(13)(14). We also curated available published data of MPI based studies from India for our comparative analysis (17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Study Detailsmentioning
confidence: 99%
“…We utilized an 8-parameter-based scale deployed in all studies for assessing MPI scores as described in study detail. In order to understand the prevalence and pattern of secondary peritonitis across India, we compared our in-house study with 10 other published studies that had used MPI scoring system from various states of India (17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Studies from different geographical locations were selected to have an idea about the epidemiological diversity of secondary peritonitis across India (Figures 1A, 1B).…”
Section: Occurrence and Associated Mortality Due To Secondary Periton...mentioning
confidence: 99%
See 1 more Smart Citation